DEVELOPMENT BLENDED E-LEARNINGSTRATEGY TO IMPROVE PRE-SERVISE BIOLOGY TEACHERS’ PROFESSIONAL EDUCATION SKILL - YENNY ANWAR (Sriwijaya University Learning and Education International Conference, 2016)
Mastering of Science Biology and learning professionals Biology to carry out the study of Biology is one of Biology education program goals.The rapid growth ofInformationand technologyare increasingly demanding high ICT skills of every citizen.Efforts to meet these needs by combining e-learning and konvensional (blended learning) strategy.Through this research, students can not only improve their professional ability but also gradually increase their ability to use ICT both in accessing, managing, integrating, and creating information. This research is used the principle ofDevelopmental Research Design.Application of blended learning is equipped with a media that is valid and practical so that it can be used independently of students.Improved preservise learning outcomes seen after implementation of blended learning program. The Student Professional Ability (PCK) also increased, though both were still in the category of pre PCK, but after the application of blended learning, the student has reached the upper limit of the pre PCK categories.This suggests that blended learning can improve learning outcomes and the professional ability of student teachers.